The Effect of Successful City Branding and MotoGP Tourism Events on Tourists' Decision to Revisit Mandalika - Achmad Mas Nugroho; Gagih Pradini (Budapest International Research and Critics University, 2022)
Mandalika is one of the special economic zones (SEZ) and is one of the super priority tourism destinations, this makes development that empowers the potential of resources successful to create city branding and the implementation of MotoGp tourism events on March 2022 attracts tourists to visit mandalika again, This study is a quantitative study to assess the degree of influence of Variable city branding (X1) with Prеsеncе, Potеntiаl, Plаcе, Pulsе, Pеoplе, Prеrеquisitе Indicators and MotoGP tourism events (X2) with indicators аttrаction, аccеsibility, dаn аmеnitiеs. on the decision to revisit (Y) with indicators of Destination Perception, Suitability of Desire, and Information &Promotion with the method of multiple linear regression analysis through the distribution of questionnaires to 100 respondents, the results of this study are known that city branding and MotoGP tourism events have a significant influence on the decision of tourists to visit Mandalika again.